COVID-19: What the World Should Learn from India? - Ipsita Mahapatra; Ramesh Nagarajappa; Debasruti Naik; Punyarupa Pati; Upasana Dhar (Indian Journal of Forensic Medicine & Toxicology, 2021)
The pandemic, COVID-19 is not the first but savagely has become a global attraction. First detected inChina, it has spread to India including other countries. Various intervention strategies like restriction ontravel, lockdown, screening and extensive research has contained the widespread infection in India. Whileintensifying preparedness for the unprecedented threat posed by COVID-19, the Government of India(GoI) has constituted an inter-ministerial committee represented by the ministers of the Ministry of Healthand Family Welfare (MoHFW), External Affairs, Home, Civil Aviation as well as the National DisasterManagement Authority. India has constantly been the centre of discussion because of the way it has handledthe pandemic so far. This article reflects the preparedness and potential plan by India to scale-up COVID-19management.